Efektifitas Penyaluran Dana ZIS : Studi Kasus pada SMA Terbuka Binaan LAZ Sukses Kota Depok - Hasan, Nurul Ichsan; Jannah, Rona Roudhotul (AL-FALAH : Journal of Islamic Economics, 2019)
Purpose: This study aims to analyze the effectiveness of the ZIS fund distribution program in the form of school operational assistance in SMA Terbuka assisted by LAZ Zakat Sukses, Depok.Design/Method/Approach: There are 4 variables that can measure the level of effectiveness in this study. Among other things, the accuracy of program targets, program socialization, program objectives, and program monitoring. The four variables fall into the range of effective value scales. That is, accuracy of program targets: 3.13. program socialization: 3.25. program objectives: 3.11. program monitoring: 2.94. Findings:  The final result of the program effectiveness level score shows a value of 3.11 .Meaning that the value is in the range of effective scales. In general, the distribution of ZIS funds in the form of operational assistance in SMA Terbuka assisted by LAZ Zakat Sukses of Depok City has been effective.Originality/Values: This study contributes extensively in introducing a measurement of how the efectivity of ZIS distribustion, especially in Terbuka Senior High School which maintained by LAZ Sukses, Depok